Compliance with legal minimum wages and overtime pay regulations in China - Linxiang Ye; Thomas Gindling; Shi Li (IZA Journal of Labor & Development, 2015)
We use a matched firm-employee data set to examine the extent of compliance with minimum wage and overtime pay regulations in Chinese formal sector firms. We find evidence that there is broad compliance with legal minimum wages in China; fewer than 3.5% of full-time workers earn less than the legal monthly minimum wage. On the other hand, we find evidence that there is substantial non-compliance with overtime pay regulations; almost 29% of the employees who work overtime are not paid any additional wage for overtime hours, and 70% are paid less than the legally-required 1.5 times the regular wage.
Keywords: J3; J8; O17; 330; China; Labor protection regulations; Minimum wages; Overtime pay; Compliance